TagP, a PAAR-domain containing protein, plays roles in the fitness and virulence of Acinetobacter baumannii - Li, Yanbing; Cui, Yiming; Song, Kai; Shen, Leiming; Xiao, Liting; Jin, Junyan; Zhao, Yanting; Yan, Yanfeng; Zhao, Shengyuan; Yao, Wenwu; Wang, Shihua; Du, Zongmin; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundType VI secretion system (T6SS) is widely present in Gram-negative bacteria and directly mediates antagonistic prokaryote interactions. PAAR (proline-alanine-alanine-arginine repeats) proteins have been proven essential for T6SS-mediated secretion and target cell killing. Although PAAR proteins are commonly found in A. baumannii, their biological functions are not fully disclosed yet. In this study, we investigated the functions of a PAAR protein termed TagP (T6SS-associated-gene PAAR), encoded by the gene ACX60_RS09070 outside the core T6SS locus of A. baumannii strain ATCC 17978.MethodsIn this study, tagP null and complement A. baumannii ATCC 17978 strains were constructed. The influence of TagP on T6SS function was investigated through Hcp detection and bacterial competition assay; the influence on environmental fitness was studied through in vitro growth, biofilm formation assay, surface motility assay, survivability in various simulated environmental conditions; the influence on pathogenicity was explored through cell adhesion and invasion assays, intramacrophage survival assay, serum survival assay, and G. melonella Killing assays. Quantitative transcriptomic and proteomic analyses were utilized to observe the global impact of TagP on bacterial status.ResultsCompared with the wildtype strain, the tagP null mutant was impaired in several tested phenotypes such as surface motility, biofilm formation, tolerance to adverse environments, adherence to eukaryotic cells, endurance to serum complement killing, and virulence to Galleria melonella. Notably, although RNA-Seq and proteomics analysis revealed that many genes were significantly down-regulated in the tagP null mutant compared to the wildtype strain, there is no significant difference in their antagonistic abilities. We also found that Histone-like nucleoid structuring protein (H-NS) was significantly upregulated in the tagP null mutant at both mRNA and protein levels.ConclusionsThis study enriches our understanding of the biofunction of PAAR proteins in A. baumannii. The results indicates that TagP involved in a unique modulation of fitness and virulence control in A. baumannii, it is more than a classic PAAR protein involved in T6SS, while how TagP play roles in the fitness and virulence of A. baumannii needs further investigation to clarify.